2016
DOI: 10.15506/jog.2016.35.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformation of Epigenetic Iron Staining: Indication of Low-Temperature Heat Treatment in Mozambique Ruby

Abstract: In the past several years, Mozambique has emerged as one of the world's most important sources of ruby, and unheated stones from this country are in particularly strong demand. Nevertheless, it is common for these rubies to undergo low-temperature heating (~1,000°C or below) to slightly improve their colour. The treated stones may show very subtle or no alteration of internal features (e.g. mineral inclusions, 'fingerprints', needles, 'silk', etc.). However, 'iron-stained' surface-reaching fractures in the rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…. The specific peaks of the main functional group are: 3696 and 3648 cm −1 for OH stretching attributed to the inner‐surface hydroxyl groups, 2873–2970 cm −1 for organic carbon, due to the incomplete burning of wood and 2517, 1795, 1448, 1067, 876, and 712 cm −1 for vibrational modes of CO groups from carbonate …”
Section: Resultsmentioning
confidence: 99%
“…. The specific peaks of the main functional group are: 3696 and 3648 cm −1 for OH stretching attributed to the inner‐surface hydroxyl groups, 2873–2970 cm −1 for organic carbon, due to the incomplete burning of wood and 2517, 1795, 1448, 1067, 876, and 712 cm −1 for vibrational modes of CO groups from carbonate …”
Section: Resultsmentioning
confidence: 99%
“…After treatment, orange epigenetic iron stains in surface-reaching fissures became darker due to the oxidation and dehydration of iron minerals at higher temperatures (figure 3H). Typically the orange iron stains consist of limonite (α-FeO(OH)) and convert to brownish red hematite (α-Fe 2 O 3 ) during heat treatment (Koivula, 2013;Sripoonjan et al, 2016). The other observed change was seen in monazite crystals, which changed color from orange-brown to near-colorless after heat treatment.…”
Section: After Heating Before Heating Sample Idmentioning
confidence: 99%
“…In contrast, heating corundum at low temperatures, sometimes below 700°C, will only subtly affect their internal inclusions, making the treatment much more challenging to detect without advanced instrumentation (figure 1). Previous studies on the effect of low-temperature heat treatment on inclusions have focused on rubies from Mozambique (Pardieu et al, 2015;Sripoonjan et al, 2016;Saeseaw et al, 2018) and blue sapphires from Madagascar (Krzemnicki, 2010;Hughes and Perkins, 2019). In these studies, rubies showed slight inclusion alterations when heated to 900°C and developed clear…”
mentioning
confidence: 99%
“…The platelets never showed alteration at 600°C, but under the conditions of this experiment the stone's color was not altered (Saeseaw et al, 2018). Fractures with iron staining showed a change from yellowish to brownish red, even when heated at low temperatures (Sripoonjan et al, 2016). However, these features are not commonly seen in faceted stones.…”
mentioning
confidence: 92%
“…Many Mugloto-type stones show this subtle color alteration, which can be removed by heat treatment (Pardieu et al, 2015;Sripoonjan et al, 2016;Saeseaw et al, 2018).…”
mentioning
confidence: 99%